HALAL FOOD RESEARCH IN INDONESIA: PUBLICATION TRENDS, THEMATIC EVOLUTION, AND EMERGING TECHNOLOGIES (2015–2026) - Erlina Pertiwi; Moh. Farih Fahmi; Maryam Bte Badrul Munir (Referensi Islamika: Jurnal Studi Islam, 2026)
This study aims to systematically map the development of halal food research in Indonesia, identify publication trends, thematic structures, and emerging technological topics, and provide directions for future research. A bibliometric analysis was conducted on 197 Scopus-indexed publications published between 2015 and 2026. Data were retrieved using a comprehensive search query covering halal food, halal certification, halal supply chain, traceability, authentication, and related topics. Following the PRISMA 2020 screening procedure, the selected publications were analyzed using Microsoft Excel and VOSviewer 1.6.20 through publication trend analysis, keyword co-occurrence mapping, clustering, overlay visualization, and density visualization. The results reveal a substantial increase in publication output during the study period, reflecting growing academic interest in halal food issues in Indonesia. Keyword co-occurrence analysis identified five thematic clusters covering halal governance and certification, consumer trust and religiosity, halal supply chain management, blockchain-enabled traceability, food safety, and halal authentication technologies. Overlay visualization indicates a gradual shift from conventional certification- and consumer-oriented studies toward technology-driven themes such as blockchain, traceability, Internet of Things, and digital halal assurance systems. Density visualization further shows that halal certification and halal supply chain remain dominant research themes, while authentication technologies such as real-time PCR, FTIR, chemometrics, and GC–MS represent emerging areas of investigation. The study relies exclusively on the Scopus database and therefore may not capture relevant publications indexed in other databases. Nevertheless, the findings provide a comprehensive overview of the intellectual structure, thematic evolution, and emerging directions of halal food research in Indonesia. This study offers an updated bibliometric mapping of halal food research in Indonesia for the 2015–2026 period and highlights the growing importance of halal governance, digital traceability, and scientific authentication technologies in strengthening halal assurance systems and supply chain integrity